A method for simultaneously determining axial permeability and transverse permeability of tight reservoir cores by canister degassing test. Issue 4 (16th December 2019) - Zhao, Yu; Wang, Chaolin; Bi, Jing
Abstract: Permeability anisotropy of shale and tight gas reservoirs is critical for applications in unconventional gas recovery, but laboratory measurements are still limited. This paper presents an experimental method for determining permeability anisotropy of shale and tight reservoirs. The method uses gas production data from a canister and an analytical solution of continuity equation in anisotropic core sample. Axial permeability and transverse permeability of the core are estimated by matching experimental data with analytical solution. The proposed method is verified by comparing with true values and calculated values through numerical simulations that cover variations in rock permeability. The method is applied to real data measured in canister degassing tests (CDT) involving two different directional shale core samples. Then, the experimental results are compared with the results from pulse pressure decay (PPD) method. Both the verification from numerically calculated results and the comparison between PPD results and CDT results exhibit the practicality of the proposed method. At last, the effects of permeability anisotropy, porosity, initial gas pressure, rock dimensions, and adsorption on the profiles of gas production are investigated. Abstract : This paper presents an experimental method for determining permeability anisotropy of shale and tight reservoirs. The method uses gas production data from a canister and an analytical solution of continuity equation in anisotropic core sample. The proposed method is verified through numerical simulations and is applied to estimate the axial permeability and transverse permeability of shale core samples.